2021
DOI: 10.1021/acsaem.1c01412
|View full text |Cite
|
Sign up to set email alerts
|

Cathode of Zn-Ni Layered Double Hydroxide Nanosheet Arrays Wrapped with a Porous NiMoSx Shell and Anode of 3D Hierarchical Nitrogen-Doped Carbon for High-Performance Asymmetric Supercapacitors

Abstract: The rational design and synthesis of multicomponent core@shell structures with fine morphology is a promising approach to develop electrode materials for advanced supercapacitors. In this study, Zn-Ni LDH@NiMoS x nanosheets with a hierarchical heterostructure are grown in situ on nickel foam through the hydrothermal routes, for the potential use as an integrated positive electrode material. The Zn-Ni LDH@NiMoS x shows a unique morphology and mesoporous feature with excellent synergistic effects between indiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 50 publications
0
19
0
Order By: Relevance
“…The additional signal positioned at ∼169.0 eV is ascribed to surface sulfate groups. 8,17 The P 2p spectrum (Figure 4i) of Ni−Co−P NAs displayed two peaks at 134.4 and 133.4 eV, which correspond to the 2p 1/2 and 2p 3/2 , respectively. 29,54 These XPS results strongly support the successful incorporation of Se, S, and P anions into the TM LDH to form TMCs and TMP architecture.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The additional signal positioned at ∼169.0 eV is ascribed to surface sulfate groups. 8,17 The P 2p spectrum (Figure 4i) of Ni−Co−P NAs displayed two peaks at 134.4 and 133.4 eV, which correspond to the 2p 1/2 and 2p 3/2 , respectively. 29,54 These XPS results strongly support the successful incorporation of Se, S, and P anions into the TM LDH to form TMCs and TMP architecture.…”
Section: Methodsmentioning
confidence: 99%
“…It is reported that NC is an excellent negative material due to its large surface area, high electron conductivity, and good electrochemical properties. 4,8 The NC negative electrode exhibited a deviated-rectangular feature within the voltage window of −1.0 to 0.0 V, featuring the electrical double-layer capacitive nature accompanied by a slight pseudocapacitive nature (Figure S17), whereas the Ni− Co−Se NAs delivered noticeable redox peaks within the window regime of −0.2 to 0.75 V, demonstrating its typical battery-like feature. 27 Therefore, the Ni−Co−Se NAs//NC hybrid device could have the potential to deliberately enlarge the working voltage window, thereby improving the energy density (Figure S17c).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…As the mechanism occurs at the electrode, the structure, quality, and nature of the electrode engage in a vital role for better supercapacitor performance . Therefore, different varieties of electrode materials like metal/metal oxides, , layered doubled hydroxides, , MXenes, , metal–organic frameworks (MOFs), MXene and MOF composites, transition metal dichalcogenide, polymers, composites of transition metal oxides with 3D graphene materials or porous carbon nanofibers, and composite of metal oxides/sulfides/phosphides/nitrides/selenides have been recently designed to achieve high-density supercapacitors.…”
Section: Introductionmentioning
confidence: 99%